Psychological type profile of Methodist churchgoers in England. Issue 6 (3rd July 2021) - Lewis, Christopher Alan; Francis, Leslie J.; Geary, Alison M.
ABSTRACT: The present study draws on data provided by 263 adults attending seven services held in Methodist churches who completed the Francis Psychological Type Scales. The profile of these Methodist churchgoers is then set alongside the profile of 3, 302 Anglican churchgoers reported in an earlier study. While the two groups shared preferences for introversion (54% and 55%) sensing (80% and 86%), feeling (60% and 64%), and judging (86% and 89%), the proportion of sensing types was significantly higher in the Methodist churches. While 72% of Anglican churchgoers reported the SJ temperament, the proportion rose significantly to 80% among Methodist churchgoers.